Bullous dermatosis in the southeastern of Turkey: A study of 125 cases - Yanatma, Irem; Sarac, Gulbahar; Vural Karatoprak, Hacer; Cenk, Hulya (Annals of Medical Research, 2022)
Aim: Autoimmune bullous diseases occur when antibodies against proteins such as desmosomes and hemidesmosomes cause separation in the skin. Detailed epidemiological studies examining these diseases are limited in our country. We aim to contribute to the demographic, clinical, and treatment data on bullous diseases from an important geographic region of our country.Materials and Methods: The data of 125 cases who were followed up with a diagnosis of bullous disease between 2006 and 2019 were evaluated retrospectively. Socio-demographic characteristics, diagnoses, age and duration of disease onset, clinical findings, accompanying systemic diseases, treatments given, and side effects related to treatment were recorded.Results: 57.6% of the patients (72 people) were diagnosed as pemphigus, 31.2% (39 people) bullous pemphigoid (BP), 8% (10 people) dermatitis herpetiformis (DH), 3.2% (4 people) linear Ig A dermatosis ( LAD). BP patients were found to be significantly older than the other patients (p: 0.002). While pemphigus, BP, and LAD were more common in women, 70% of DH patients were men. Malignancy was detected in 2.8% of pemphigus patients and 5.1% of BP patients. Accompanying autoimmune disease was found in 9.7% of pemphigus patients, 17.9% of BP patients, and 20% of DH patients. The only systemic steroid was used in 20.8% of pemphigus patients, and azathioprine as a conventional agent was used in 76.4% with systemic steroid. Rituximab was started in patients who did not respond to therapy. The systemic steroid was used in 35.9% of BP patients, and azathioprine with systemic steroid was used in 43.6% of BP patients. Doxycycline was added to the treatment in 41% of the patients. Rituximab was used in 5 (12.8%) patients.Conclusion: Since our study is the first data obtained on bullous diseases from the southeastern Anatolia region, it is useful for the literature in terms of providing a basis for future studies.
Keywords: bullous dermatosis; bullous pemphigoid; pemphigus vulgaris; dermatitis herpetiformis